Reflection of cultural practices on syntactical values: an introduction to the application of space syntax to vernacular Malay architecture - Asif, Nayeem; Utaberta, Nangkula; Sabil, Azmal; Ismail, Sumarni (Elsevier, 2018)
This study introduces the basic concepts and terminologies regarding space syntax research through a simple spatial configuration. The concepts are elaborated for intricate configurations. This study aims to deepen the understanding of how syntactical analysis can extract social information embedded in traditional architectural practice in the Malay Archipelago. The basic terminologies are outlined, and the sequential procedure for analysis is described along with its interpretation in the context of actual social phenomena. Result shows that the syntactical properties of a particular configuration within a particular region reflect the traditions of the people in that region. This study serves as a basis for the future study of the applications of space syntax to diverse spatial configurations in the Malay Archipelago.